(untitled) (Research, Society and Development, 2025)
Introduction: Hospitalized elderly patients often have difficulty with oral feeding, and in some cases, an alternative route of nutrition, such as enteral feeding, is indicated. This can cause metabolic changes leading to anabolic reactions and culminating in Refeeding Syndrome (RFS).Objectives: To assess hospitalized patients over 60 years old who required a transition from oral to nasoenteral feeding, and the frequency of Refeeding Syndrome (RFS) onset.Methods: An ecological, observational, analytical, and prospective study of 100 elderly individuals (over 60 years old) hospitalized in general wards of a philanthropic hospital who required nasoenteral feeding, recruited through the hospital’s nutrition department. RFS was characterized by a serum reduction in potassium, magnesium, and phosphate levels of 10–20% (mild), 20–30% (moderate), or over 30% (severe), with or without organ dysfunction, within three to five days after reintroducing caloric intake that had been previously restricted.Results: A total of 100 patients were included, with a mean age of 75±9 years (range 60–99), 56% were women, 24% had dementia, and 81% had an infection. Among the included patients, 26% developed RFS; however, only 25% of these received preventive measures or treatment with thiamine (p = 0.001). Frail patients accounted for 42.3% of those who developed RFS. The most commonly used diet was normocaloric and normoproteic (75%).Conclusion: RFS is a frequent condition in frail hospitalized elderly patients, mainly due to a lack of awareness regarding its prevention and management in those requiring enteral replacement nutrition.